Effect of temperature on thermal oxidation behavior of biomedical Ti-Zr-Mo alloys - Correa, D. R.N.; Grandini, C. R. [UNESP]; Rocha, L. A.; Proença, J. P. [UNESP]; Sottovia, L. [UNESP]; Cruz, N. C. [UNESP]; Rangel, E. C. [UNESP]; Hanawa, T. (Elsevier, 2022)
In this study, the effect of temperature on the morphology, crystal structure, chemical composition, roughness, wettability, Vickers microhardness, and corrosion resistance of thermally oxidized Ti-15Zr-xMo (x = 0, 5, 10, and 15 wt%) samples were evaluated. Thermal oxidation treatments were performed in air, at temperatures between 773 K and 1173 K, for 21.6 ks. Oxide layers were composed preferentially by Ti, with traces of Zr, in TiO2 and ZrO2. The temperature and bulk chemical composition influenced the phase composition, showing formation of different fractions of TiO2 (anatase and rutile) together small amounts of tetragonal and monoclinic ZrO2. The morphology showed the presence of a smooth inner layer with some oxide precipitates in the outer layer, with thickness ranging from 1 µm to more than 100 µm. Roughness and contact angle values changed according to the growth of precipitates in the oxide layers. Vickers microhardness exhibited a sharp increase with the growth of the oxide layers, remaining higher than that for bulk samples. The results indicated that a favorable combination of surface properties could be achieved when optimizing the thermal oxidation treatment, which could assist in broadening the biomedical applications of the Ti-15Zr-Mo based alloys.Ti-15Zr-15Mo alloy thermally oxidized at 973 K exhibited enhanced corrosion resistance, and emerged as the best candidate for use as orthopedical implants.
Keywords: Biomaterial; Surface Modification; Thermal Oxidation; Ti Alloy